2019
DOI: 10.1093/ajh/hpz115
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Prevents Hypertension and Disrupts the Correlation Between Vascular Sympathetic Activity and Age-Related Increase in Blood Pressure in SHRs

Abstract: BACKGROUND Hypertension usually accompanies the elevated sympathetic activity and sleep interruption. Few researches explored the dynamic changes and possible correlations in cardiovascular functions and sleep patterns during the development of hypertension. In contrast, exercise training provides several benefits on cardiovascular and sleep function in hypertensive subjects. However, controlling various factors during a long period of exercise training is difficult in hypertensive subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…It is now a documented fact that regular exercise prevents hypertension by disrupting the correlation between sympathetic activity and agerelated increasing blood pressure. 20 A strong negative correlation was observed with number of days of exercise and duration of exercise with raised blood pressure in this study. Results of meta-analysis showed similar findings.…”
Section: Discussionsupporting
confidence: 60%
“…It is now a documented fact that regular exercise prevents hypertension by disrupting the correlation between sympathetic activity and agerelated increasing blood pressure. 20 A strong negative correlation was observed with number of days of exercise and duration of exercise with raised blood pressure in this study. Results of meta-analysis showed similar findings.…”
Section: Discussionsupporting
confidence: 60%
“…It is already established that SHR is characterized by neural alterations ( Bertagnolli et al, 2006 ; Masson et al, 2015 ; Duchatsch et al, 2021 ), accompanied by cardiac remodeling ( Pagan et al, 2015 ; Silva et al, 2017 ; Li et al, 2019 ; Duchatsch et al, 2021 ) and vessel structural and functional alterations ( Melo et al, 2003 ; Amaral and Michelini, 2011 ), which contribute to increase blood pressure. In the first part of the present study, we confirmed some previous results that SHR had higher BP, accompanied by an autonomic imbalance to the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training is a worldwide non-pharmacological strategy to control hypertension, recognized by societies of hypertension ( Whelton et al, 2018 ; Williams et al, 20182018 ; Sharman et al, 2019 ; Unger et al, 2020 ; Barroso et al, 2021 ). Aerobic exercise is the major component of the training for hypertension and the mechanisms involved are restoration of baroreflex activity, normalization of the autonomic imbalance to the heart ( Masson et al, 2016 ; Ferreira-Junior et al, 2019 ) reduction of the higher sympathetic drive to the vessels ( Li et al, 2019 ; Miotto et al, 2021b ; Duchatsch et al, 2021 ), skeletal muscle arterioles remodeling ( Amaral and Michelini, 2011 ; Miotto et al, 2021b ), and capillary angiogenesis ( Amaral and Michelini, 2011 ; Miotto et al, 2021b ) among others. In addition, aerobic training has been shown to prevent and/or reverse arterial stiffness not only in hypertension, but in metabolic syndrome and aging ( Moraes-Teixeira Jde et al, 2010 ; Hasegawa et al, 2018 ; Guers et al, 2019 ; Miotto et al, 2021b ; Gioscia-Ryan et al, 2021 ; Lopes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, brisk walking may have a greater impact on DBP in the elderly. This phenomenon may be due to the high basal BP in elderly participants; it may also be due to the increase in the vascular sympathetic activity with increasing age, which also has a stronger effect with exercise, showing that BP drops more significantly after exercise [27,28] . Thus, brisk walking is beneficial for BP control regardless of sex and age.…”
Section: Discussionmentioning
confidence: 99%